(untitled) - Moyise, Steve (London, 2010)
An accessible introduction to the various ways that scripture is used in Paul's theology and argumentation. It considers how particular texts were influential for Paul's understanding of God's purposes for the world, along with key themes such as the constitution of the church, the nature of faith and the role of the Law.
Keywords: Bible -- Old Testament -- Relation to the Epistles of Paul